Diagnostic Procedures and Management of Dry Eye - Kaštelan, Snježana (Hindawi Publishing Corporation, 2013)
Dry eye disease or dysfunctional tear syndrome is among the most frequent diagnoses in ophthalmology. It is a multifactorial disease of the ocular surface and tear film which results in ocular discomfort, visual disturbances, and tear instability with potential damage to the cornea and conjunctiva. Risk factors for dry eye syndrome include age, sex (female gender), race, contact lens wear, environment with low humidity, systemic medications, and autoimmune disorders. The aim of this paper is to present the systematic classification, epidemiology, diagnostic procedures, and advances in the management of dry eye disease. The recent improvements in comprehending the underlying etiologic factors will inevitably improve future classifications and diagnostic abilities leading to more effective therapeutic options. Treatment of this highly prevalent condition can drastically improve the quality of life of individuals and prevent damage to the ocular surface.